APPLICATION OF THE GREEN LEAN SIX SIGMA AND FACTORIAL EXPERIMENTS APPROACH TO IMPROVE THE QUALITY OF THE BOTTLED DRINKING WATER PROCESS - Maria Ulfah; Faula Arina; Lita Riani Hafsha (Jurnal Teknologi Industri Pertanian)
Based on the data, the highest percentage of PT.X 220 ml cup AMDK products in 2022 will reach 7200 products with a defect percentage of 0.5% of the production amount where the production amount exceeds the set limit of 0.5%.The objectives of this research are to determine waste, dominant waste and green waste, determine CTQ, determine the DPMO value and sigma value, determine the factors causing product defects, determine the waste produced, and provide suggestions for improvements to the production process and suggestions for improvements for reduce waste.Problem solving in this research uses the green lean six sigma method and factorial experiments. Based on the results of the seven waste questionnaire, it was found that the dominant waste was defect waste, while the green waste that occurred was water, material and garbage. There are 4 CTQs focusing on the type of leaking defect. The DPMO value is 1139.6 with a sigma value of 4.551. Factors that cause defective products are man, machine, method and material factors. The waste produced is water, cups and cardboard waste. Improvement proposals are prioritized on optimal machine settings using factorial experiments. The optimal machine settings are temperature 200℃ and speed 11,520 pcs/hour. Improvements are to overcome waste include collecting waste in a warehouse and selling it regularly.